Linking priority areas and land restoration options to support desertification control in northern China - Xu, Duanyang; Wang, Yuanqing; Wang, Ziyu (Ecological indicators, 2022)
•A framework for linking priority areas and land restoration options for desertification control were designed.•Sensitivity, cost and benefit were used to determine the priority area.•Land restoration options were classified by water resources capacity and land cover.•High priority areas and land restoration options were located at pixel level in northern China. Identifying priority areas and allocating suitable measures to control desertification can improve the efficiency and precision of land restoration when funds are limited. However, few studies have attempted to link priority areas and land restoration options to support desertification control at the national level. In this study, a framework was designed to identify priority areas for desertification control by integrating land sensitivity and cost and benefit indicators and then allocate eight land restoration options based on land use type and water resources capacity. The framework was validated in northern China and successfully linked priority areas and land restoration options to support desertification control. In northern China, regions with high priority for desertification control accounted for only 11.5% of the total area and were scattered in central and northwestern areas. Of those high priority areas, 51.2% should be protected without further disturbance, which were primarily distributed in the western part of northern China. Other regions could be moderately developed within the water resources capacity, including development of the ecological industry. In addition, comprehensive policies or projects, including desert national parks, land ownership confirmation, and green finance policy, should be initiated to augment the effects of desertification control and support regional economic development.